2019
DOI: 10.1016/j.envint.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The association between natural gas well activity and specific congenital anomalies in Oklahoma, 1997–2009

Abstract: Background: Natural gas drilling may pose multiple health risks, including congenital anomalies, through air pollutant emissions and contaminated water. Two recent studies have evaluated the relationship between natural gas activity and congenital anomalies, with both observing a positive relationship. Objectives: We aimed to evaluate whether residence near natural gas wells is associated with critical congenital heart defects (CCHD), neural tube defects (NTD), and oral clefts in Oklahoma, the third highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Several recent studies have suggested that living near OGD during pregnancy may elevate the risk of adverse birth outcomes, including preterm birth (Casey et al 2016;Whitworth et al 2018), small-for-gestational age (SGA) birth (Stacy et al 2015;Tran et al 2020), low birth weight (Hill 2018;Tran et al 2020), and neural tube defects (Janitz et al 2019;Mckenzie et al 2014). However, the findings have not been consistent across studies: McKenzie et al (2014), Stacy et al (2015), and Tran et al (2020) found no association with preterm birth, and Casey et al (2016) and Whitworth et al (2018) found no association with SGA.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several recent studies have suggested that living near OGD during pregnancy may elevate the risk of adverse birth outcomes, including preterm birth (Casey et al 2016;Whitworth et al 2018), small-for-gestational age (SGA) birth (Stacy et al 2015;Tran et al 2020), low birth weight (Hill 2018;Tran et al 2020), and neural tube defects (Janitz et al 2019;Mckenzie et al 2014). However, the findings have not been consistent across studies: McKenzie et al (2014), Stacy et al (2015), and Tran et al (2020) found no association with preterm birth, and Casey et al (2016) and Whitworth et al (2018) found no association with SGA.…”
Section: Introductionmentioning
confidence: 98%
“…2020 ), low birth weight ( Hill 2018 ; Tran et al. 2020 ), and neural tube defects ( Janitz et al. 2019 ; Mckenzie et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examining the relationship between unconventional OGD and birth outcomes provide suggestive evidence of adverse effects. Although study designs vary, most have characterized OGD exposure based on the density and distance of HF shale gas wells near the maternal residence in urban and rural Colorado (McKenzie et al 2014, Pennsylvania (Casey et al 2015;Currie et al 2017;Hill 2018;Ma 2016;Stacy et al 2015), Oklahoma (Janitz et al 2019), and urban Texas (Walker Whitworth et al 2018. Among the 10 studies, 8 evaluated our outcomes of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Model 3 includes environmental indicators and community-level factors in addition to the maternal characteristics. As unconventional natural gas developments (UNGD) have been associated with birth defects in Texas and other states, we included density of UNGD wells within 1 km radius of maternal address as a potential environmental exposure that might be contributing to spatial patterns (Janitz, Dao, Campbell, Stoner, & Peck, 2019;McKenzie et al, 2014;McKenzie, Allshouse, & Daniels, 2019;Rabinowitz et al, 2015;Steinzor, Subra, & Sumi, 2013;Tang, Langlois, & Vieira, 2020;Weinberger, Greiner, Walleigh, & Brown, 2017). We included average daily vehicle miles traveled (DVMT) for trucks by county as a measure of traffic-related air pollution; DVMT data were collected from the Texas Department of Transportation for 2005 through 2011 and data for all the years were averaged for a single county-level measure (Texas Department of Transportation, 2019).…”
Section: Discussionmentioning
confidence: 99%